Translatome profiling in dormant and nondormant sunflower (Helianthus annuus) seeds highlights post‐transcriptional regulation of germination. Issue 4 (26th August 2014) - Layat, Elodie; Leymarie, Juliette; El‐Maarouf‐Bouteau, Hayat; Caius, José; Langlade, Nicolas; Bailly, Christophe
Summary Seed dormancy, which blocks germination in apparently favourable conditions, is a key regulatory control point of plant population establishment. As germination requires de novo translation, its regulation by dormancy is likely to be related to the association of individual transcripts to polysomes. Here, the polysome‐associated mRNAs, that is, the translatome, were fractionated and characterized with microarrays in dormant and nondormant sunflower (Helianthus annuus) embryos during their imbibition at 10°C, a temperature preventing germination of dormant embryos. Profiling of mRNAs in polysomal complexes revealed that the translatome differs between germinating and nongerminating embryos. Association of transcripts with polysomes reached a maximum after 15 h of imbibition; at this time‐point 194 polysome‐associated transcripts were specifically found in nondormant embryos and 47 in dormant embryos only. The proteins corresponding to the polysomal mRNAs in nondormant embryos appeared to be very pertinent for germination and were involved mainly in transport, regulation of transcription or cell wall modifications. This work demonstrates that seed germination results from a timely regulated and selective recruitment of mRNAs to polysomes, thus opening novel fields of investigation for the understanding of this developmental process.